Integrated xenosurveillance of Loa loa, Wuchereria bancrofti, Mansonella perstans and Plasmodium falciparum using mosquito carcasses and faeces: A pilot study in Cameroon. - Joseph Pryce; Nils Pilotte; Benjamin Menze; Allison R Sirois; Michael Zulch; Jean Pierre Agbor; Steven A Williams; Charles S Wondji; Lisa Reimer (PLoS Neglected Tropical Diseases)
Background Community presence of loiasis must be determined before mass drug administration programmes for lymphatic filariasis and onchocerciasis can be implemented. However, taking human blood samples for loiasis surveillance is invasive and operationally challenging. A xenosurveillance approach based on the molecular screening of mosquitoes and their excreta/feces (E/F) for Loa loa DNA may provide a non-invasive method for detecting the community presence of loiasis. Methods We collected 770 wild mosquitoes during a pilot study in a known loiasis transmission area in Mbalmayo, Cameroon. Of these, 376 were preserved immediately while 394 were kept in pools to collect 36-hour E/F samples before processing. Carcasses and E/F were screened for L. loa DNA. To demonstrate this method's potential for integrated disease surveillance, the samples were further tested for Wuchereria bancrofti, Mansonella perstans, and Plasmodium falciparum. Results Despite limited sample numbers, L. loa DNA was detected in eight immediately-stored mosquitoes (2.13%; 95% CI 1.08 to 4.14), one carcass stored after providing E/F (0.25%; 95% CI 0.04 to 1.42), and three E/F samples (estimated prevalence 0.77%; 95% CI 0.15 to 2.23%). M. perstans and P. falciparum DNA were also detected in carcasses and E/F samples, while W. bancrofti DNA was detected in E/F. None of the carcasses positive for filarial worm DNA came from pools that provided a positive E/F sample, supporting the theory that, in incompetent vectors, ingested parasites undergo a rapid, complete expulsion in E/F. Conclusions Mosquito xenosurveillance may provide a useful tool for the surveillance of loiasis alongside other parasitic diseases.